Hubungan Kesadaran Diri dengan Perilaku Social Loafing pada Siswa SMKN 1 Martapura - Kamilda; Mulyani; Miftahul Aula Sa’adah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This research is motivated by the existence of social loafing behavior in students in group learning, namely the tendency of individuals to reduce effort and responsibility when working together, which is thought to be influenced by self-awareness. This study aims to determine the level of self-awareness, the level of social loafing behavior, and the relationship between the two in students of SMKN 1 Martapura. This study uses a quantitative approach with a field research type, with a population of 601 students and a sample of 239 students determined through cluster random sampling techniques. Data collection uses a Likert scale questionnaire, while data analysis uses the Pearson Product Moment correlation test with the help of SPSS 25. The results show that the level of self-awareness is in the high category and social loafing is in the low category, and there is a negative and significant relationship between self-awareness and social loafing behavior, with a correlation coefficient value of r = 0.652 and a significance of 0.000 (p < 0.05). This indicates that the higher the student's self-awareness, the lower their tendency to engage in social loafing, so increasing self-awareness is important to support the effectiveness of group learning.